OIL SHALE FROM CALDERA LAKES OF DIATREMES - Streltsova G.D. (My University, 2001)
The chemical composition of oil shales from caldera lakes facies, as well as the carbon and oxygen isotope composition of rock-forming carbonates and sulfur isotope composition of pyrite from fine veinlets have been studied. Rocks of clayey, clayey-carbonate and carbonate composition have been differentiated. High P2O5 and TiO2 content of shales should be emphasized. Oil shales are characterized by rather high concentrations of Ni, Co, Cr, V, Cu and Sr, and pyrites - by very high concentrations of As, Mo, Cu and Ag and a light sulfur isotope composition. Rock-forming carbonates show a heavy carbon isotope composition and rather heavy oxygen isotope composition uncommon with non-marine formations. The above geochemical peculiarities are due to the oil shales formation under special conditions of caldera lakes situated over diatremes.